Предмет: Алгебра,
автор: MansurS
Разложите на множители выражение:
1) (x - y)(x + y) + 2(x +3y) - 8
2) (a - 3b)(2a + 3b) -4(a + 3b) - 3
Ответы
Автор ответа:
0
1) (x - y)(x + y) + 2(x +3y) - 8=x^2-y^2+2x+6y-8
2) (a - 3b)(2a + 3b) -4(a + 3b) - 3=2a^2+3ab-6ab-9b^2-4a-12b-3=2a^2-3ab-9b^2-4a-12b-3
2) (a - 3b)(2a + 3b) -4(a + 3b) - 3=2a^2+3ab-6ab-9b^2-4a-12b-3=2a^2-3ab-9b^2-4a-12b-3
Похожие вопросы
Предмет: Математика,
автор: lolyatupaya07
Предмет: Русский язык,
автор: armaanchik
Предмет: Математика,
автор: loldetpul
Предмет: История,
автор: IAmDuCnEP0ne
Предмет: Математика,
автор: Angel061106